Aturan Sertifikasi Produk Halal dalam Tinjauan Maqāṣid al-Syarī’ah Jasser Auda - Musthofa, Moh. Aqil (Al-Faruq: Jurnal Hukum Ekonomi Syariah dan Hukum Islam, 2022)
The development of the food industry in Indonesia is very rapid, but in fact some of the products in circulation have not received halal certificates. LPPOM MUI as the only institution that implements halal certification, at that time received criticism for being considered slow in responding to this development. In 2014, the government issued Halal Product Guarantee Law which provides a rule that all products circulating in Indonesia must be halal certified from BPJPH, which is an official institution under the Ministry of Religious Affairs. The awareness of the Indonesian Muslim community towards halal products is very high, because consuming something halal is an obligation of Sharia. This paper describes the purpose and wisdom of establishing the rules for the obligation to certify halal products with the theory of Jasser Auda's maqāṣid al-syarī'ah. This research resulted in a conclusion: first, there is a general purpose (al-maqāṣid al-'āmmah) that should take precedence (ḍarūrῑyyah) namely the protection of the soul (ḥifẓ al-nafsi) and protection of property (ḥifẓ al-māl). Second, the specific purpose (al-maqāṣid al-khāṣṣah) is the protection of consumers from illicit products, as well as improving the economy and welfare for halal product business actors. Third, the partial goal (al-maqāṣid al-juz'iyyah) is a work ethic with full responsibility, obtaining blessings in producing and consuming halal products, and obtaining blessings from Allah Almighty.